Right Ventricular Failure and Pathobiology in Patients with Congenital Heart Disease – Implications for Long-Term Follow-Up - Köhler, Doreen; Arnold, Raoul; Loukanov, Tsvetomir; Gorenflo, Matthias (Frontiers in Pediatrics, 2013)
Right ventricular dysfunction represents a common problem in patients with congenital heart defects, such as Tetralogy of Fallot or pulmonary arterial hypertension. Patients with congenital heart defects may present with a pressure or volume overloaded right ventricle in a biventricular heart or in a single ventricular circulation in which the right ventricle serves as systemic ventricle. Both subsets of patients are at risk of developing right ventricular failure. Obtaining functional and morphological imaging data of the right heart is technically more difficult than imaging of the left ventricle. In contrast to findings on mechanisms of left ventricular dysfunction, very little is known about the pathophysiologic alterations of the right heart. The two main causes of right ventricular dysfunction are pressure and/or volume overload of the right ventricle. Until now, there are no appropriate models available analyzing the effects of pressure and/or volume overload on the right ventricle. This review intends to summarize clinical aspects mainly focusing on the current research in this field. In future, there will be increasing attention to individual care of patients with right heart diseases. Hence, further investigations are essential for understanding the right ventricular pathobiology.